Azotobacter population, soil nitrogen and groundnut growth in mercury-contaminated tailing inoculated with Azotobacter - Reginawanti Hindersah; Zellya Handyman; Febby Nur Indriani; Pujawati Suryatmana; Nenny Nurlaeny (Journal of Degraded and Mining Lands Management, 2018)
Gold mine tailing in Buru island, Maluku Province, Indonesia contains high level of mercury but low in carbon and plant nutrients. Revegetation in such condition needs certain soil treatment which is suitable for plant growth. The objective of pot trials was to study the effect of indigenous Plant Growth Promoting Rhizobacteria Azotobacter and organic matter on bacterial survival as well as growth of groundnut grown in mine tailing. The experimental design was a Split Plot Design which tested three types of Azotobacter liquid inoculant and three soil total organic carbon (TOC) contents. Results showed that Azotobacter inoculation increased Azotobacter population in tailing at the end of vegetative growth of groundnut. Total nitrogen content in soil decreased when TOC level increased. However, nitrogen uptake and growth of groundnut did not change after Azotobacter inoculation or manure amendment. These experiments provided information that Azotobacter inoculation on groundnut maintain its proliferation in Hg-contaminated mine tailing.